2005
DOI: 10.1161/01.hyp.0000153051.56460.6a
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Inhibition Attenuates Oxidative Stress but Not Hypertension Produced by Chronic ET-1

Abstract: Abstract-Experiments were conducted to test the hypothesis that hypertension produced by chronic ET-1 infusion is mediated by NADPH oxidase-dependent superoxide production. Mean arterial pressure (MAP) was continuously monitored in male Sprague Dawley rats by telemetry. After baseline measurements, rats were placed on a high-salt diet (8% NaCl) and osmotic minipumps were implanted to infuse ET-1 (5 pmol/kg per minute intravenous) for 12 days. Control rats were maintained on the high-salt diet only. Separate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 31 publications
3
97
0
1
Order By: Relevance
“…Interestingly, deletion of ecSOD results in oxidative stress and hypertension, whereas gene transfer to SHRs ameliorates hypertension. We and others also observed that tempol fails to "treat hypertension" (61,358), although it has multiple beneficial effects, including reduction of oxidative stress, improvement in insulin sensitivity, reduction of myocardial remodeling, etc. This illustrates the complex relation between oxidative stress and hypertension and requires further clarification through studies.…”
Section: Pathologic Role Of Ros In Hypertensionmentioning
confidence: 83%
“…Interestingly, deletion of ecSOD results in oxidative stress and hypertension, whereas gene transfer to SHRs ameliorates hypertension. We and others also observed that tempol fails to "treat hypertension" (61,358), although it has multiple beneficial effects, including reduction of oxidative stress, improvement in insulin sensitivity, reduction of myocardial remodeling, etc. This illustrates the complex relation between oxidative stress and hypertension and requires further clarification through studies.…”
Section: Pathologic Role Of Ros In Hypertensionmentioning
confidence: 83%
“…32 In vitro studies 33 suggest that the increase in reduced nicotinamide-adenine dinucleotide phosphate oxidase activity is ET A mediated and, hence, may be increased when plasma ET-1 levels are raised. However, whether superoxide contributes significantly to BP in models of exogenous 34,35 or endogenous 32,36 elevation of ET-1 remains controversial. Our experiments confirm the results of previous transgenic studies demonstrating that an isolated increase in plasma ET-1 does not result in hypertension in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…51 Similarly, chronic ET-1 infusion is associated with elevations in reactive oxygen species, although reports disagree as to the extent to which oxidative stress contributes to the associated hypertension. 36,52 Whereas hypertension associated with chronic ET B receptor blockade can be inhibited by ET A receptor antagonists, evidence for a role of oxidative stress, or specifically superoxide, is not straightforward. Williams et al recently observed that the superoxide dismutase mimetic, tempol, attenuated the hypertension associated with ET B receptor blockade in rats on a high-salt diet, but only during the initial days of treatment.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%
“…Elmarakby et al have recently demonstrated that apocynin inhibits the increase in oxidative stress associated with chronic ET-1 infusion, yet the resulting hypertension was unaffected. 52 …”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%